2020
DOI: 10.1080/01652176.2020.1714096
|View full text |Cite
|
Sign up to set email alerts
|

Peste des petits ruminants in large ruminants, camels and unusual hosts

Abstract: Since its first report in 1942, peste-des-petits-ruminants virus (PPRV) has caused several epidemics in a wide range of susceptible hosts around the world. In the last 30 years, the evidence of natural and experimental infections and virus isolation were reported from novel but unusual hosts such as camel, cattle, buffalo, dogs, Asiatic lion and pigs. In addition, PPRV in a potential vector, biting midges (Culicoides imicola), has been reported. Either presented as clinical and/or subclinical infections, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…The virus generally causes infection in small ruminants worldwide (Al-Majali et al, 2008;Megersa et al, 2011;Intisar et al, 2017); however, it also has the propensity to cause infection in wild ungulates (Aziz-ul-Rahman et al, 2018, Rahman, 2019 and other unusual hosts such as buffalo, cattle (Balamurugan et al, 2014) and camels (Omani et al, 2019). Indeed, there exists a controversy regarding clinical infection of PPRV in camels (Ul-Rahman et al, 2020). A few studies have reported an occurrence of natural clinical infection with a mortality ranging from 60%−90% (Khalafalla et al, 2010: Saeed et al, 2015, whereas another study claimed an absolute lack of clinical infection upon experimental exposure .…”
Section: Discussionmentioning
confidence: 99%
“…The virus generally causes infection in small ruminants worldwide (Al-Majali et al, 2008;Megersa et al, 2011;Intisar et al, 2017); however, it also has the propensity to cause infection in wild ungulates (Aziz-ul-Rahman et al, 2018, Rahman, 2019 and other unusual hosts such as buffalo, cattle (Balamurugan et al, 2014) and camels (Omani et al, 2019). Indeed, there exists a controversy regarding clinical infection of PPRV in camels (Ul-Rahman et al, 2020). A few studies have reported an occurrence of natural clinical infection with a mortality ranging from 60%−90% (Khalafalla et al, 2010: Saeed et al, 2015, whereas another study claimed an absolute lack of clinical infection upon experimental exposure .…”
Section: Discussionmentioning
confidence: 99%
“…Peste des petits ruminants (PPR) is a highly contagious transboundary disease caused by the Peste des petits ruminants virus (PPRV) [1][2][3]. PPRV belongs to the morbillivirus genus, Paramyxoviridae family [4] and has been renamed as small ruminant morbillivirus (SRMV) by the International Committee on Taxonomy of Viruses in 2016 [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the recent-past PPRV has been reported to infect not only goats and sheep, but also camels [13], cattle [14], water buffalo [15,16], and wildlife species, including African buffalo [17,18], saiga antelope [19,20], dorcas gazelles [19,21], gemsbok [22], Nubian ibex [23], and some other wild ungulate species [19,20]. Reports of PPRV detection in Asiatic lions [24] and dogs [3,25] may reflect contamination of their food with infected ruminants, but their competence as hosts has not been established [13,[26][27][28][29]. Goats and sheep are the main hosts for PPRV and play a major role in its transmission and global epidemiology.…”
Section: Introductionmentioning
confidence: 99%
“…It is caused by the peste des petits ruminants virus (PPRV) and affects mainly small domestic ruminants (sheep and goats) as well as camels, with serious economic loss especially in many countries of Africa and Asia (1,2). Wild ruminants, such as gazelles, deer, roe deer, antelope can also be affected (3)(4)(5)(6)(7)(8)(9)(10)(11)(12), which consequently poses a further risk for the control and surveillance in vaccination programs.…”
Section: Introductionmentioning
confidence: 99%